Association Between Serum LDL-C and ApoB and SYNTAX Score in Patients With Stable Coronary Artery Disease. (September 2018) - Lin, Taiwu; Wang, Luzhao; Guo, Jingbin; Liu, Peng; Chen, Liheng; Wei, Mengqiu; Li, Gongxin
The aim of this study was to examine the relationship between low-density lipoprotein cholesterol (LDL-C) and apolipoprotein (Apo) B levels and the SYNergy between percutaneous coronary intervention with TAXus and cardiac surgery (SYNTAX) score (SS) in patients with stable angina pectoris. We enrolled 594 patients who were suspected to have coronary heart disease (CHD) and who underwent coronary angiography. Patients were divided into 4 groups based on the SS: normal (SS = 0, n = 154), low SS (SS ≤ 22, n = 210), intermediate SS (22 < SS < 32, n = 122), and high SS (SS ≥ 33, n = 63). Positive correlations between lipoprotein (a), LDL-C, ApoB, total cholesterol, and SS were significant ( r = 0.132, 0.632, 0.599, and 0.313, respectively; P < .01), whereas high-density lipoprotein cholesterol (HDL-C), ApoA1, and ApoA1/ApoB levels showed a significant negative correlation ( r = −0.29, −0.344, and −0.561, respectively; P < .01). Multivariate linear regression analysis revealed that LDL-C, ApoB, ApoA1/ApoB, fibrinogen (Fg), and HDL-C levels had an effect on SS (standardized regression coefficients were 0.41, 0.29, −0.12, 0.08, and −0.09, respectively; P < .05). In conclusion, LDL-C, ApoB, ApoA1/ApoB, Fg, and HDL-C levels affected the SS and were predictors of CHD complexity.